Optical signature of erythrocytes by light scattering in microfluidic flows1. Issue 16 (21st August 2015) - Dannhauser, D.; Rossi, D.; Causa, F.; Memmolo, P.; Finizio, A.; Wriedt, T.; Hellmers, J.; Eremin, Y.; Ferraro, P.; Netti, P. A.
<x xml:space="preserve">Abstract</x> Label-free analysis of individual erythrocytes by a camera-based light scattering approach coupled with a viscoelasticity-induced cell migration technique in microfluidic flows.